Virtual self-conversation using motivational interviewing techniques to promote healthy eating and physical activity: A usability study - Anastasiadou, Dimitra; Herrero, Pol; Vázquez-De Sebastián, Julia; Garcia-Royo, Paula; Spanlang, Bernhard; Álvarez de la Campa, Elena; Slater, Mel; Ciudin, Andreea; Comas, Marta; Ramos-Quiroga, J. Antoni; Lusilla-Palacios, Pilar (Frontiers in Psychiatry, 2023)
We aim to examine the usability of a Virtual Reality (VR) platform, called ConVRSelf, which has been designed to address the needs of People Living With Obesity (PLWO). Fourteen participants with a desire to eat healthier and exercise more (6 normal weight and 8 PLWO; Mean age = 41.86, SD = 13.89) were assigned to the experimental group (EG) or the control group (CG). EG participants, after being trained on motivational interviewing skills, engaged in a virtual self-conversation using embodiment and body swapping techniques, which aimed to normalize and resolve their ambivalence to change lifestyle habits. CG participants, embodied in their virtual bodies, participated in a pre-established discourse with a virtual counsellor giving them psychoeducational advice about how to change lifestyle habits. A mixed-methods design was used, involving a semi-structured interview and self-report questionnaires, including readiness to change habits (Readiness Rulers), body ownership (Body Ownership Questionnaire, BOQ), and system usability (System Evaluation Questionnaire, SEQ). Thematic content analysis was carried out for qualitative data while statistical data analysis was carried out using SPSS 20.0. Participants from both groups showed high readiness to change lifestyle (Readiness Rulers) before engaging with the virtual experiences, which was maintained at the same level after the interventions and their scores on the SEQ and BOQ were satisfactory. Regarding qualitative information obtained from the interviews, almost all participants found the VR experience to be novel, interesting, and enjoyable. A higher acceptability was observed among PLWO from the EG than normal weight participants from the same group, a promising finding for the ConVRSelf platform, which had been specifically designed to address the needs of PLWO. The ConVRSelf system is well-accepted by participants and is ready to be tested with PLWO in a clinical setting.